Highland barley straw adsorbent as well as preparation method and application thereof
By treating barley straw with potassium chloride and hemicellulase, a highly efficient barley straw adsorbent was prepared, solving the problem of easy saturation and difficult regeneration of traditional adsorbents, and realizing the efficient removal of TVOC and the environmentally friendly application of the material.
Patent Information
- Application Number
- CN202411424782.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-10
AI Technical Summary
Existing adsorbents are easily saturated when removing volatile organic compounds (TVOCs), are difficult to regenerate, and pose a risk of secondary pollution. The use of traditional materials increases treatment costs and damages forest resources.
By treating barley straw with potassium chloride-assisted hemicellulase, and by controlling the potassium chloride concentration and soaking time, the surface and internal structure of barley straw were modified, increasing porosity and active sites, thus preparing a barley straw adsorbent with high adsorption performance.
It achieves efficient removal of TVOC, solves the problem of adsorbent saturation and difficulty in regeneration, reduces costs and secondary pollution, and realizes resource utilization and environmental protection of agricultural waste.
Smart Images

Figure CN119281298A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adsorbents, and particularly relates to a highland barley straw adsorbent and a preparation method and application thereof. Background Art
[0002] With the acceleration of industrialization and the improvement of urbanization, the emission of volatile organic compounds, or TVOC, has become increasingly prominent, causing serious impacts on the environment and human health. TVOC is a type of pollutant widely present in indoor air, mainly from building decoration materials, furniture, paints, and detergents. Long-term exposure to TVOC can cause headaches, dizziness, nausea, and even cancer in severe cases.
[0003] Traditional TVOC treatment methods mainly include physical adsorption, chemical adsorption and biodegradation. Although the traditional adsorbent prepared by the existing technical method has good adsorption performance, as the adsorption process proceeds, the adsorbent will gradually reach a saturated state, and the traditional adsorbent in the saturated state cannot be desorbed, resulting in the inability to continue to use after reaching adsorption saturation, and frequent replacement is required, which not only increases the processing cost, but also has the risk of causing secondary pollution. In addition, the traditional adsorbent itself is a non-renewable resource, especially the activated carbon obtained by calcining biomass in an anaerobic environment, which is at the cost of cutting down trees and destroying forest resources, limiting its application in large-scale and long-term TVOC treatment. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a highland barley straw adsorbent and its preparation method and application. The present invention adopts a potassium chloride-assisted hemicellulase modification method, controls the potassium chloride concentration and the immersion time, and introduces hemicellulase for enzymatic hydrolysis, thereby creating a rich pore structure on the surface and inside of the highland barley straw, increasing the active sites on the adsorbent surface, and improving the selective adsorption of TVOC. Not only can TVOC in the air be effectively removed, but also the problems of traditional adsorbents being easily saturated and difficult to recycle and causing secondary pollution during use are solved, thus achieving efficient utilization of agricultural waste resources, friendly environmental protection, and significant improvement of treatment effects.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is:
[0006] The first object of the present invention is to provide a method for preparing a highland barley straw adsorbent, comprising the following steps:
[0007] S1. Cleaning samples: Rinse highland barley straw under running water to remove dust and impurities on the surface of the highland barley straw.
[0008] S2. High-temperature cooking: The cleaned highland barley straw is placed in boiling water for cooking to remove impurities and some soluble substances on the surface of the highland barley straw.
[0009] S3, soaking treatment: preparing a potassium chloride solution, and soaking the cooked highland barley straw in the potassium chloride solution to soften and change the surface charge properties of the cooked highland barley straw, thereby obtaining soaked highland barley straw.
[0010] S4. Hemicellulase heat treatment: prepare a hemicellulase solution, place the soaked highland barley straw in the hemicellulase solution for degradation treatment, and obtain degraded highland barley straw; wherein the mass concentration of the hemicellulase solution is 0.1 mg / mL to 0.5 mg / mL.
[0011] S5. Enzyme inactivation treatment: placing the degraded highland barley straw in a water bath for enzyme inactivation treatment to obtain a highland barley straw adsorbent.
[0012] S6. Adjusting pH: Rinse the highland barley straw adsorbent with deionized water several times until it becomes neutral.
[0013] S7. Drying and crushing samples: The washed highland barley straw adsorbent is placed in a blast drying oven to dry and then crushed.
[0014] Preferably, the concentration of the potassium chloride solution in the soaking treatment in step S3 is 0.07 mol / L to 0.24 mol / L, and the soaking time is 25 min to 35 min. Potassium chloride, as a neutral salt, does not introduce additional hydrogen ions and hydroxide ions into the aqueous solution, thereby avoiding the change of pH during pretreatment. At the same time, the potassium chloride solution can promote the breaking of the connecting bonds between lignin and carbohydrates, making the microstructure of the highland barley straw looser, which is conducive to the subsequent improvement of adsorption performance.
[0015] Preferably, the time for the hemicellulase heat treatment in step S4 is 30 minutes. If the degradation time is too short, the micropore and mesopore structure inside the highland barley straw will not be fully exposed, resulting in insufficient adsorption capacity; and if the degradation time is too long, the highland barley straw structure will be over-degraded, destroying its adsorption performance.
[0016] Preferably, the temperature of the enzyme inactivation treatment in step S5 is 70° C. and the time is 20 min.
[0017] Preferably, in step S6, the highland barley straw after enzyme inactivation treatment is rinsed to neutrality and then dried and crushed at 80°C.
[0018] The second object of the present invention is to provide a highland barley straw adsorbent prepared by the above preparation method.
[0019] Preferably, the particle size of the highland barley straw adsorbent is 18 mesh to 100 mesh.
[0020] The third object of the present invention is to provide the use of the above-mentioned highland barley straw adsorbent in the preparation of TVOC adsorbent.
[0021] Preferably, the highland barley straw adsorbent is placed in an air atmosphere containing TVOC for adsorption treatment.
[0022] Preferably, the ratio of the mass of highland barley straw adsorbent to the amount of TVOC is 1g to 5g: 1.6mg / m 3 ~1.97 mg / m 3 .
[0023] Preferably, the ratio of the mass of highland barley straw adsorbent to the amount of TVOC is 2g:1.8mg / m 3 .
[0024] Preferably, the adsorption treatment is carried out under the following conditions: adsorption for 30 min to 150 min at room temperature.
[0025] Preferably, the particle size of the highland barley straw adsorbent is 40 mesh, the adsorption temperature is 28° C., and the adsorption time is 30 min.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. The present invention provides a method for preparing a highland barley straw adsorbent, wherein the highland barley straw is placed in a potassium chloride solution for salting out treatment, and then degraded in a hemicellulase solution, and then degraded and degraded, and then the highland barley straw adsorbent is obtained by drying and crushing. The highland barley straw adsorbent prepared by the preparation method of the present invention can not only effectively remove TVOC in the air, but also solve the problems that traditional adsorbents are easily saturated during use, cannot be used after saturation, need frequent replacement, high cost, and cause secondary pollution, thereby achieving efficient utilization of agricultural waste resources, friendly environmental protection, and significant improvement of governance effects, and providing a basis for the development of new environmentally friendly materials.
[0028] Among them, the purpose of soaking in potassium chloride solution is to soften and change the surface charge properties of highland barley straw through ion exchange or osmosis, and promote the adsorption and degradation of hemicellulase; hemicellulase can degrade the hemicellulose component in highland barley straw, making its fiber structure looser and forming more micropores and mesopores. These pore structures have increased specific surface area and higher surface energy, and can adsorb TVOC molecules on their surface through van der Waals forces.
[0029] 2. The present invention provides a highland barley straw adsorbent, which can not only effectively remove TVOC in the air, but also has the advantages of simple preparation, low cost and easy regeneration. Among them, the surface of the highland barley straw adsorbent contains functional groups such as hydroxyl and carboxyl, which can react with TVOC molecules such as hydrogen bonds and acid-base reactions to form strong chemical bonding forces, thereby firmly adsorbing TVOC molecules on the surface of the highland barley straw adsorbent.
[0030] 3. The present invention also uses highland barley straw adsorbent to remove TVOC in the air, which has better adsorption performance and good green and low-carbon environmental protection characteristics than the existing technologies such as diatomaceous earth, activated carbon, bamboo charcoal and macroporous adsorption resin AB-8; when the particle size of the highland barley straw adsorbent is 40 mesh, the addition amount is 2g, the adsorption temperature is 28℃, the adsorption time is 30min, and the initial TVOC content is 1.8mg / m 3 The removal effect is best and the adsorption effect is best. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a graph showing the TVOC removal rate of highland barley straw adsorbents in Examples 1 to 7 and 10 to 13.
[0032] Figure 2 This is a diagram showing the adsorption effect of highland barley straw adsorbent on TVOC in Example 6 of the present invention. Figure 2 (a) is the effect of the particle size of highland barley straw adsorbent on the TVOC adsorption effect, (b) is the effect of the amount of highland barley straw adsorbent added on the TVOC adsorption effect, (c) is the effect of the adsorption temperature of highland barley straw adsorbent on the TVOC adsorption effect, (d) is the effect of the adsorption time of highland barley straw adsorbent on the TVOC adsorption effect, and (e) is the effect of the initial TVOC content on the TVOC adsorption effect of highland barley straw adsorbent.
[0033] Figure 3 The scanning electron microscope images of highland barley straw and highland barley straw adsorbent of Example 6 before and after adsorption are shown in FIG. Figure 3 (a) is a scanning electron microscope image of highland barley straw, (b) is a scanning electron microscope image of highland barley straw adsorbent before adsorption, and (c) is a scanning electron microscope image of highland barley straw adsorbent after adsorption.
[0034] Figure 4 It is the infrared analysis diagram of highland barley straw and the highland barley straw adsorbent of Example 6 before and after adsorption.
[0035] Figure 5 This is a relationship diagram between the initial TVOC content and the adsorption amount of the highland barley straw adsorbent in Example 6.
[0036] Figure 6 This is the isotherm diagram of TVOC adsorption by highland barley straw adsorbent in Example 6, Figure 6 (a) is the Langmuir isotherm diagram of TVOC adsorption by highland barley straw adsorbent, and (b) is the Freundlich isotherm diagram of TVOC adsorption by highland barley straw adsorbent.
[0037] Figure 7 This is a graph showing the change in the adsorption amount of TVOC by the highland barley straw adsorbent in Example 6 over time.
[0038] Figure 8 The following are the fitting diagrams of the adsorption kinetic equation of TVOC by highland barley straw adsorbent in Example 6, wherein (a) is a pseudo-first-order kinetic equation curve diagram, and (b) is a pseudo-second-order kinetic equation curve diagram.
[0039] Fig. 9 This is a curve diagram showing the variation of the adsorption amount of the highland barley straw adsorbent in Example 6 with the adsorption temperature.
[0040] Fig.10 This is the fitting diagram of the thermodynamic equation for TVOC adsorption by highland barley straw adsorbent in Example 6.
[0041] Fig.11 This is a comparison chart of the adsorption effects of different adsorption materials on TVOC in Example 6.
[0042] Fig.12 This is the analysis and regeneration diagram of the highland barley straw adsorbent in Example 6.
[0043] Fig.13 This is a diagram showing the adsorption effect of the highland barley straw adsorbent prepared in Comparative Examples 1 to 5 on TVOC.
[0044] Fig.14 This is a diagram showing the adsorption effect of the highland barley straw adsorbent prepared in Comparative Examples 6 to 10 on TVOC.
[0045] Fig.15 This is a diagram showing the adsorption effect of the highland barley straw adsorbent prepared in Example 5 and Example 10 to Example 13 on TVOC.
[0046] Fig.16 This is a diagram showing the adsorption effect of the highland barley straw adsorbent prepared in Comparative Examples 11 to 15 on TVOC. DETAILED DESCRIPTION
[0047] The technical solution of the present invention will be clearly and completely described below in combination with the data in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] It should be noted that the professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, the various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.
[0049] Existing technologies usually use traditional materials such as activated carbon, diatomaceous earth, and bamboo charcoal as adsorbents to remove TVOC from the air. However, although these traditional adsorbents have good adsorption performance, as the adsorption process proceeds, the adsorbents will gradually reach a saturated state, resulting in a significant decrease in adsorption efficiency and the need for frequent replacement, which not only increases the treatment cost, but also poses a risk of causing secondary pollution, thus limiting their application in large-scale, long-term treatment of total volatile organic pollutants.
[0050] In view of the problems existing in the prior art, the present invention proposes a method for preparing a highland barley straw adsorbent, which comprises the following steps: placing highland barley straw in a potassium chloride solution for salting-out treatment to soften and change the surface charge properties of the highland barley straw to obtain soaked highland barley straw; placing the soaked highland barley straw in a hemicellulase solution for degradation treatment to obtain degraded highland barley straw; wherein the mass concentration of the hemicellulase solution is 0.1 mg / mL to 0.5 mg / mL; performing enzyme inactivation treatment on the degraded highland barley straw, drying, and crushing to obtain the highland barley straw adsorbent.
[0051] The present invention prepares a highland barley straw adsorbent by a method of potassium chloride-assisted hemicellulase treatment. Wherein, soaking in a potassium chloride solution helps to further open the microstructure of the highland barley straw, increase the porosity and specific surface area, and these increased pores become effective sites for adsorbing TVOC molecules; the enzymatic hydrolysis of the hemicellulase solution can degrade the hemicellulose components in the highland barley straw, not only remove part of the non-cellulose components, reduce the competitive sites in the adsorption process, but also promote the rearrangement of the cellulose structure and the formation of a microporous structure. More tiny and uniform pores are generated on the surface and inside of the highland barley straw after enzymolysis, and these pores have a stronger capillary effect and can more effectively capture and fix TVOC molecules; in addition, potassium chloride also plays a role of an auxiliary catalyst in the enzymolysis process, and promotes the enzymolysis reaction of the hemicellulase by softening and changing the surface charge properties of the highland barley straw, so that the enzymolysis effect is more significant. The preparation method of the highland barley straw adsorbent of the present invention not only retains good physical adsorption characteristics, but also exhibits excellent TVOC adsorption capacity due to its unique pore structure and chemical properties, thereby overcoming the problems of traditional adsorbents being easily saturated during use, difficult to regenerate, and causing secondary pollution.
[0052] The technical solution of the present invention is further explained by using embodiments below, which are specifically as follows:
[0053] Example 1
[0054] A method for preparing a highland barley straw adsorbent comprises the following steps:
[0055] S1. Cleaning samples: Weigh 30 g of highland barley straw and rinse it under running water to remove dust and impurities on the surface of the highland barley straw.
[0056] S2. High temperature cooking: Cook the washed highland barley straw in boiling water for 30 minutes.
[0057] S3. Soaking treatment: Soak the cooked highland barley straw in a 0.2 mol / L potassium chloride solution for 35 minutes.
[0058] S4. Hemicellulase heat treatment: The soaked highland barley straw was placed in 500 mL of a hemicellulase solution with a mass concentration of 0.2 mg / mL, and enzymolyzed in a water bath at 60° C. for 30 min.
[0059] S5. Enzyme inactivation treatment: Place the enzymatically hydrolyzed highland barley straw in a 70°C water bath for 20 minutes to inactivate the enzyme.
[0060] S6. Adjusting pH: Rinse the highland barley straw after enzyme inactivation treatment with deionized water for multiple times until it becomes neutral.
[0061] S7. Drying and crushing the sample: Place the washed highland barley straw in a blast drying oven and dry it at 80° C., then crush it and pass it through an 18-mesh sieve to obtain a highland barley straw adsorbent.
[0062] Example 2
[0063] A method for preparing a highland barley straw adsorbent has the same preparation steps as those in Example 1, except that the soaking time in S3 is replaced from 35 min to 25 min.
[0064] Example 3
[0065] A method for preparing a highland barley straw adsorbent has the same preparation steps as those of Example 1, except that the concentration of the potassium chloride solution is replaced from 0.2 mol / L to 0.1 mol / L.
[0066] Example 4
[0067] A method for preparing a highland barley straw adsorbent has the same preparation steps as those of Example 3, except that the soaking time is replaced from 35 min to 25 min.
[0068] Example 5
[0069] A method for preparing a highland barley straw adsorbent has the same preparation steps as those of Example 1, except that the concentration of the potassium chloride solution is replaced from 0.2 mol / L to 0.15 mol / L, and the soaking time is replaced from 35 min to 30 min.
[0070] On the basis of Example 5, 11 groups of parallel tests were conducted, and the average removal rate of the prepared highland barley straw adsorbent was 8.59%.
[0071] Example 6
[0072] A method for preparing a highland barley straw adsorbent is the same as the preparation steps of Example 5, except that the concentration of the potassium chloride solution is replaced from 0.15 mol / L to 0.07 mol / L, the mass concentration of hemicellulose is 0.22 mg / mL, and the 18-mesh sieve in step S7 is replaced by a 40-mesh sieve.
[0073] Example 7
[0074] A method for preparing a highland barley straw adsorbent has the same preparation steps as those of Example 5, except that the concentration of the potassium chloride solution is replaced from 0.15 mol / L to 0.24 mol / L.
[0075] Example 8
[0076] A method for preparing a highland barley straw adsorbent has the same preparation steps as those of Example 5, except that the soaking time is replaced from 30 min to 21.5 min.
[0077] Example 9
[0078] A method for preparing a highland barley straw adsorbent has the same preparation steps as those of Example 5, except that the soaking time is replaced from 30 min to 38.5 min.
[0079] Example 10
[0080] A method for preparing a highland barley straw adsorbent has the same preparation steps as those of Example 5, except that the mass concentration of the hemicellulose solution is replaced from 0.2 mg / mL to 0.1 mg / mL, and the 18-mesh sieve in step S7 is replaced by a 100-mesh sieve.
[0081] Embodiment 11
[0082] A method for preparing a highland barley straw adsorbent has the same preparation steps as those of Example 5, except that the mass concentration of the hemicellulose solution is replaced from 0.2 mg / mL to 0.3 mg / mL.
[0083] Example 12
[0084] A method for preparing a highland barley straw adsorbent has the same preparation steps as those of Example 5, except that the mass concentration of the hemicellulose solution is replaced from 0.2 mg / mL to 0.4 mg / mL.
[0085] Example 13
[0086] A method for preparing a highland barley straw adsorbent has the same preparation steps as those of Example 5, except that the mass concentration of the hemicellulose solution is replaced from 0.2 mg / mL to 0.5 mg / mL.
[0087] Comparative Example 1
[0088] A method for preparing a highland barley straw adsorbent, which adopts an alkali-heat method to prepare the highland barley straw adsorbent, comprises the following steps:
[0089] S1. Cleaning samples: Weigh highland barley straw and rinse it under running water to remove dust and impurities on the surface of the highland barley straw.
[0090] S2. High temperature cooking: Cook the washed highland barley straw in boiling water for 0.5 h.
[0091] S3. Alkali heat treatment: The cooked highland barley straw is placed in a 0.1 mol / L caustic soda solution and soaked at 60° C. for 0.5 h for alkaline heat treatment.
[0092] S4. Adjusting pH: Rinse the highland barley straw after alkali heat treatment with deionized water for multiple times until it becomes neutral.
[0093] S6. Drying and crushing samples: Place the washed highland barley straw in a blast drying oven and dry at 80° C. for 24 hours, then crush it and pass it through a 40-mesh sieve to obtain a highland barley straw adsorbent.
[0094] Comparative Example 2
[0095] A method for preparing a highland barley straw adsorbent is the same as the preparation method of comparative example 1, except that the concentration of the caustic soda solution in S3 is 0.2 mol / L.
[0096] Comparative Example 3
[0097] A method for preparing a highland barley straw adsorbent is the same as the preparation method of comparative example 1, except that the concentration of the caustic soda solution in S3 is 0.3 mol / L.
[0098] Comparative Example 4
[0099] A method for preparing a highland barley straw adsorbent is the same as the preparation method of comparative example 1, except that the concentration of the caustic soda solution in S3 is 0.4 mol / L.
[0100] Comparative Example 5
[0101] A method for preparing a highland barley straw adsorbent is the same as the preparation method of comparative example 1, except that the concentration of the caustic soda solution in S3 is 0.5 mol / L.
[0102] Comparative Example 6
[0103] A method for preparing a highland barley straw adsorbent, which adopts an acid-coenzyme method to prepare the highland barley straw adsorbent, comprises the following steps:
[0104] S1. Cleaning samples: Weigh highland barley straw and rinse it under running water to remove dust and impurities on the surface of the highland barley straw.
[0105] S2. High temperature cooking: Cook 6 g of cleaned highland barley straw in boiling water for 0.5 h.
[0106] S3. Acidification treatment: The cooked highland barley straw is placed in a 0.15 mol / L citric acid solution and soaked for 0.5 h for acidification treatment.
[0107] S4. Ligninase heat treatment: The acidified highland barley straw was placed in 500 mL of a ligninase solution with a mass concentration of 4 mg / mL, and subjected to enzymatic hydrolysis in a water bath at 50° C. for 0.5 h.
[0108] S5. Enzyme inactivation treatment: Place the enzymatically hydrolyzed highland barley straw in a 70°C water bath for 10 minutes to inactivate the enzyme.
[0109] S6. Adjusting pH: Rinse the highland barley straw after enzyme inactivation treatment with deionized water for multiple times until it becomes neutral.
[0110] S7. Drying and crushing the sample: Place the washed highland barley straw in a blast drying oven to dry at 80° C., crush it, and pass it through a 40-mesh sieve to obtain a highland barley straw adsorbent.
[0111] Comparative Example 7
[0112] A method for preparing a highland barley straw adsorbent is the same as the preparation method of Comparative Example 6, except that the concentration of ligninase in S4 is 8 mol / L.
[0113] Comparative Example 8
[0114] A method for preparing a highland barley straw adsorbent is the same as the preparation method of Comparative Example 6, except that the concentration of ligninase in S4 is 12 mol / L.
[0115] Comparative Example 9
[0116] A method for preparing a highland barley straw adsorbent is the same as the preparation method of Comparative Example 6, except that the concentration of ligninase in S4 is 16 mol / L.
[0117] Comparative Example 10
[0118] A method for preparing a highland barley straw adsorbent is the same as the preparation method of Comparative Example 6, except that the concentration of ligninase in S4 is 20 mol / L.
[0119] Comparative Example 11
[0120] A method for preparing a highland barley straw adsorbent, which adopts a salting-out coenzyme method to prepare the highland barley straw adsorbent, comprises the following steps:
[0121] S1. Cleaning samples: Weigh highland barley straw and rinse it under running water to remove dust and impurities on the surface of the highland barley straw.
[0122] S2. High temperature cooking: Cook 6 g of cleaned highland barley straw in boiling water for 0.5 h.
[0123] S3. Salting-out treatment: The cooked highland barley straw was placed in a 0.1 mol / L CaCl solution and soaked for 0.5 h for salting-out treatment.
[0124] S4. Adjusting pH: Rinse the highland barley straw after salting out with deionized water for several times until it becomes neutral.
[0125] S5. Lignin peroxidase heat treatment: The highland barley straw after salting out was placed in 500 mL of a cellulase solution with a mass concentration of 0.1 mg / mL, and subjected to enzymatic hydrolysis in a water bath at 50° C. for 0.5 h.
[0126] S6. Enzyme inactivation treatment: Place the enzymatically hydrolyzed highland barley straw in a 75°C water bath for 10 minutes to inactivate the enzyme.
[0127] S7. Adjusting pH: Rinse the highland barley straw after enzyme inactivation treatment with deionized water for multiple times until it becomes neutral.
[0128] S8. Drying and crushing samples: Place the washed highland barley straw in a blast drying oven and dry at 80° C., then crush it and pass it through a 40-mesh sieve to obtain a highland barley straw adsorbent.
[0129] Comparative Example 12
[0130] A method for preparing a highland barley straw adsorbent is the same as the preparation method of Comparative Example 11, except that the mass concentration of cellulase in S5 is 0.2 mg / mL.
[0131] Comparative Example 13
[0132] A method for preparing a highland barley straw adsorbent is the same as the preparation method of Comparative Example 11, except that the mass concentration of cellulase in S5 is 0.3 mg / mL.
[0133] Comparative Example 14
[0134] A method for preparing a highland barley straw adsorbent is the same as the preparation method of Comparative Example 11, except that the mass concentration of cellulase in S5 is 0.4 mg / mL.
[0135] Comparative Example 15
[0136] A method for preparing a highland barley straw adsorbent is the same as the preparation method of Comparative Example 11, except that the mass concentration of cellulase in S5 is 0.5 mg / mL.
[0137] On the basis of the single factor experiment, the concentration of hemicellulase solution (X1), potassium chloride solution concentration (X2) and soaking time (X3) were selected as optimization factors. The quadratic regression orthogonal rotation combination design table was obtained using DPS software. 23 different highland barley straw adsorbents were prepared, and 23 groups of experiments were designed to evaluate the removal rate of highland barley straw adsorbents, as shown in Tables 1 and 2.
[0138] Table 1 Quadratic regression orthogonal rotation combination design table
[0139] Experiment No. <![CDATA[X2: Initial concentration of potassium chloride (mol / L)]]> <![CDATA[X3: Immersion time (min)]]> Removal rate (%) Example 1 1(0.2) 1(35) 11.64 Example 2 1(0.2) -1(25) 10.04 Example 3 -1(0.1) 1(35) 11.52 Example 4 -1(0.1) -1(25) 9.75 Example 1 1(0.2) 1(35) 9.52 Example 2 1(0.2) -1(25) 10.44 Example 3 -1(0.1) 1(35) 11.94 Example 4 -1(0.1) -1(25) 10.64 Example 5 0(0.15) 0(30) 9.75 Example 5 0(0.15) 0(30) 9.15 Example 6 -1.682(0.07) 0(30) 10.25 Example 7 1.682(0.24) 0(30) 9.64 Example 8 0(0.15) -1.682(21.5) 10.48 Example 9 0(0.15) 1.682(38.5) 9.81 Example 5 0(0.15) 0(30) 8.47 Example 5 0(0.15) 0(30) 8.16 Example 5 0(0.15) 0(30) 8.91 Example 5 0(0.15) 0(30) 9.09 Example 5 0(0.15) 0(30) 7.85 Example 5 0(0.15) 0(30) 8.17 Example 5 0(0.15) 0(30) 7.85 Example 5 0(0.15) 0(30) 8.20 Example 5 0(0.15) 0(30) 8.93
[0140] Using DPS, we conducted statistical analysis on the experimental results in Table 1 and observed that the regression equation was: Y = 8.38675-0.04387X1-0.24926X2+0.19208X3+0.52965X1 2 +0.68699X2 2 +0.77537X3 2 +0.37875X1X2+0.37375X1X3-0.29875X2X3
[0141] Table 2 ANOVA table
[0142]
[0143] It can be seen from Table 2 that F1=3.678<F0.05(5,8)=3.69, that is, the regression relationship reaches an extremely significant level, indicating that the model is reliable and its prediction results are accurate; in the model, F2(6.303.)>F0.01(9,13)(4.19), that is, it is extremely significant at the 0.01 level, this model is reliable and can be used for experimental prediction.
[0144] In addition, X2 2 、X32 and X1 2 At the 1% significance level, a very significant difference is shown. The design has orthogonality, and there is no correlation between the regression coefficients. Under the condition of significance level α=0.10, the present invention further eliminates insignificant items, performs quadratic analysis of variance, and constructs a simplified regression equation:
[0145] Y=8.38675+0.52965X1 2 +0.68699X2 2 +0.77537X3 2
[0146] In order to further evaluate the influence of the interaction among X1, X2, and X3 on the comprehensive score of removal efficiency Y and determine the optimal level range of each factor, the corresponding response surface diagram was drawn based on the analysis results.
[0147] Figure 1 This is the effect of hemicellulase concentration and initial potassium chloride concentration on the removal rate. Figure 1 The results showed that when the potassium chloride concentration remained unchanged, the removal rate of TVOC by highland barley straw adsorbent decreased first and then increased with the increase of hemicellulase; when the hemicellulase was fixed, the removal rate of TVOC by highland barley straw adsorbent decreased first and then increased with the increase of potassium chloride concentration. When the mass concentration of hemicellulase was 0.3 mg / mL and the initial concentration of potassium chloride was 0.2 mol / L, the minimum removal rate of TVOC by highland barley straw adsorbent was 8.3868%.
[0148] Through a variance analysis (as shown in Table 2), the combination of the three factors (X1, X2, X3) affected the adsorption effect to varying degrees. In particular, when comparing the interactions between X1X3 and X2X3, the interaction between X2X1 reached a very significant level, that is, P<0.01, which means that the effect of the initial concentration of hemicellulase and the initial concentration of potassium chloride on the adsorption results reached a very significant level, as shown in Table 3.
[0149] Table 3 Effect of hemicellulase concentration and initial potassium chloride concentration on removal rate
[0150] <![CDATA[Horizontal X1X2]]> -1.6818 -1.3409 -1 -0.5 0 0.5 1 1.3409 1.6818 1.682 11.8279 11.12 10.5718 10.0566 9.8848 10.0566 10.5718 11.12 11.8279 1.341 11.2822 10.5743 10.0261 9.5108 9.3391 9.5108 10.0261 10.5743 11.2822 1 10.8595 10.1516 9.6034 9.0882 8.9164 9.0882 9.6034 10.1516 10.8595 0.5 10.4623 9.7544 9.2062 8.6909 8.5192 8.6909 9.2062 9.7544 10.4623 0 10.3298 9.622 9.0737 8.5585 8.3868 8.5585 9.0737 9.622 10.3298 -0.5 10.4623 9.7544 9.2062 8.6909 8.5192 8.6909 9.2062 9.7544 10.4623 -1 10.8595 10.1516 9.6034 9.0882 8.9164 9.0882 9.6034 10.1516 10.8595 -1.341 11.2822 10.5743 10.0261 9.5108 9.3391 9.5108 10.0261 10.5743 11.2822 -1.682 11.8279 11.12 10.5718 10.0566 9.8848 10.0566 10.5718 11.12 11.8279
[0151] The DPS software measured the optimal preparation factors of potassium chloride and hemicellulase: X1 = -1.682, X2 = -1.682, X3 = -1.682. Under these three factors, the adsorption effect of highland barley straw adsorbent was the strongest, which was 14.02%. It was verified according to the predicted results. Under the conditions of potassium chloride concentration of 0.07 mol / L, hemicellulase mass concentration of 0.22 mg / mL, and soaking time of 21.5 min, highland barley straw adsorbent was used for verification and mass preparation. After verification, the removal rate was 13.78%. The ratio of the two values is 0.97, which is approximately = 1, indicating that the values between the two are consistent and the verification is successful, indicating that the model has extremely high authenticity.
[0152] (1) Specific surface area and pore size (BET) analysis:
[0153] Table 4 Analysis of specific surface area and pore size parameters of highland barley straw adsorbent in Example 6
[0154]
[0155]
[0156] The highland barley straw adsorbent of Example 6 was further measured by BET analysis, and the specific surface area was found to be 1.489 m 2 / g, pore volume 0.004cm 3 / g, and the pore size distribution is mainly concentrated at 3.289d, which further proves that the highland barley straw adsorbent has a large number of adsorption sites and has a significant effect on the adsorption of TVOC.
[0157] Taking the highland barley straw adsorbent prepared in Example 6 of the present invention as an example, it is applied to the removal of TVOC in the air. The specific application method and results are as follows:
[0158] (1) Single factor test:
[0159] a. Effect of particle size on TVOC adsorption
[0160] The crushed highland barley straw adsorbent was passed through 18-mesh, 40-mesh, 60-mesh, 80-mesh and 100-mesh sieves respectively, and 2 g of highland barley straw adsorbent with different particle sizes was weighed and placed in a culture dish. When the TVOC content in the sealed box reached 1.8 mg / m 3 When the highland barley straw adsorbent was placed in a closed box for 30 minutes, the removal rate was calculated.
[0161] b. Effect of addition amount on TVOC adsorption
[0162] Weigh 1.0g, 1.5g, 2.0g, 2.5g, 3.0g, and 40-mesh highland barley straw adsorbents respectively and place them in culture dishes. When the TVOC content in the sealed box reaches 1.8mg / m 3 , the highland barley straw adsorbent was placed in a closed box for 30 minutes, and the removal rate was calculated.
[0163] c. Effect of temperature on TVOC adsorption
[0164] Weigh five portions of 2g, 40-mesh highland barley straw adsorbent respectively, and wait until the TVOC content in the sealed box reaches 1.8mg / m 3 , set the temperatures to 20℃, 24℃, 26℃, 28℃, and 30℃, respectively, and adsorb for 30 minutes, and calculate the removal rate.
[0165] d. Effect of adsorption time on TVOC adsorption
[0166] Weigh five portions of 2g, 40-mesh highland barley straw adsorbent and wait for the TVOC content in the sealed box to reach 1.8mg / m 3 The highland barley straw adsorbent was placed in a closed box and adsorbed for 30 min, 60 min, 90 min, 120 min, and 150 min, respectively, and the removal rate was calculated.
[0167] e. Effect of TVOC content on TVOC adsorption
[0168] Weigh five portions of 2g, 40-mesh highland barley straw adsorbent and set the TVOC content to 1.6mg / m in a closed box at room temperature. 3 , 1.7mg / m 3 , 1.8mg / m 3 , 1.9mg / m 3 , 1.97mg / m 3 When the specified TVOC content value is reached, the highland barley straw adsorbent is placed in a closed box for adsorption for 30 minutes, and the removal rate is calculated.
[0169] Figure 2 These are the adsorption effect diagrams of the highland barley straw adsorbent on TVOC in Example 6 of the present invention, (a) is the influence diagram of the particle size of the highland barley straw adsorbent on the adsorption effect of TVOC, (b) is the influence diagram of the amount of highland barley straw adsorbent added on the adsorption effect of TVOC, (c) is the influence diagram of the adsorption temperature of the highland barley straw adsorbent on the adsorption effect of TVOC, (d) is the influence diagram of the adsorption time of the highland barley straw adsorbent on the adsorption effect of TVOC, and (e) is the influence diagram of the initial TVOC content on the adsorption effect of the highland barley straw adsorbent on TVOC.
[0170] Depend on Figure 2(a) It was found that the removal rate of highland barley straw adsorbent was the highest and the best when the particle size was 40 mesh, reaching a very significant level (F=43.544, P<0.01); after the particle size exceeded 40 mesh, the removal rate decreased slowly with the increase of particle size.
[0171] Depend on Figure 2 (b) It was concluded that as the amount of highland barley straw adsorbent added increased, its removal rate initially increased, but after the amount of highland barley straw adsorbent added reached a certain mass point, its removal rate gradually stabilized. The effect of different amounts of highland barley straw adsorbent added on the TVOC removal rate was extremely significant (F=21.281, P<0.01); and the removal rates of 3g, 2.5g, and 2g were significantly better than other additions, and the removal rate of 1g was the lowest.
[0172] Depend on Figure 2 (c) It was found that the removal rate of highland barley straw adsorbent increased with the increase of adsorption temperature. The removal rate was the highest at 28°C, showing the best adsorption effect. The effect of adsorption temperature on TVOC adsorption effect was extremely significant (F=89.669, P<0.01).
[0173] Depend on Figure 2 (d) It was concluded that the removal rate of highland barley straw adsorbent increased with the extension of adsorption time, and F=306.739, P<0.01. At 120min and 150min, the removal rate of TVOC by highland barley straw adsorbent was significantly better than that at 30min and 60min, while there was no significant difference between 120min and 90min. At 150min, the removal rate of TVOC by highland barley straw adsorbent reached 22.62%; the removal rate was the lowest at 30min, reaching 13.77%.
[0174] Depend on Figure 2 (e) The initial TVOC content of highland barley straw adsorbent was 1.97 mg / m 3 The adsorption effect was the best when the removal rate reached 13.98%; F = 22.327, P < 0.01. 3 TVOC reaches adsorption saturation in a closed box with fixed volume.
[0175] Table 5 Elemental analysis of highland barley straw and highland barley straw adsorbent of Example 6 before and after adsorption
[0176]
[0177] It can be seen from Table 5 that highland barley straw contains a large amount of C and H elements, followed by a small amount of N and S elements. Compared with highland barley straw, the N and S content in highland barley straw adsorbent is significantly reduced. Comparing the element proportions before and after adsorption of highland barley straw adsorbent, it can be seen that the elements mainly composed of C and H and some ions have changed, and ions have exchanged during the process of TVOC adsorption by highland barley straw adsorbent, proving that the adsorption process of this experiment is a mixed adsorption combining physical and chemical adsorption.
[0178] Figure 3 The scanning electron microscope images of highland barley straw and highland barley straw adsorbent of Example 6 before and after adsorption are shown in FIG. Figure 3 (a) is a scanning electron micrograph of highland barley straw, (b) is a scanning electron micrograph of highland barley straw adsorbent before adsorption, and (c) is a scanning electron micrograph of highland barley straw adsorbent after adsorption. Figure 3 (a) It is concluded that the surface of highland barley straw is loose and rough, and there are many pore structures that provide adsorption sites for adsorption; Figure 3 (b) It is concluded that the highland barley straw adsorbent has a richer internal structure than highland barley straw and can adsorb more substances. This structure can provide more attachment sites for the adsorption process. Figure 3 (c) It was concluded that the surface of highland barley straw adsorbent became smooth after adsorbing TVOC.
[0179] Figure 4 The infrared analysis graphs of highland barley straw and the highland barley straw adsorbent of Example 6 before and after adsorption. A is the infrared analysis graph of highland barley straw, B is the infrared analysis graph before adsorption of the highland barley straw adsorbent, and C is the infrared analysis graph after adsorption of the highland barley straw adsorbent. The group changes of highland barley straw and highland barley straw adsorbent before and after adsorption of TVOC were further analyzed by FTIR infrared spectroscopy. It was observed from A that highland barley straw has abundant chemical groups; it was observed from B and C that before and after adsorption of highland barley straw adsorbent, the hydroxyl groups increased significantly after modification and showed a very strong peak characteristic. At 3500cm -1 In the wavelength region, the hydroxyl group showed a significant shift phenomenon. This change proves that after the highland barley straw adsorbent adsorbs TVOC, its hydroxyl structure is reconstructed or rearranged, resulting in a change in the vibration frequency of the hydroxyl group in the molecule, thereby causing specific peaks in the infrared spectrum to be enhanced or weakened.
[0180] a. Adsorption isotherm
[0181] Common models in adsorption equilibrium are the Langmuir and Freundlich isotherms.
[0182] The Langmuir isotherm is expressed as:
[0183]
[0184] The Freundlich isotherm is expressed as follows:
[0185] q=K·C 1 / n (2)
[0186] Taking the logarithm of both sides of the above equation can turn it into a linear form:
[0187] lgq=lgk+(1 / n)lgC (3)
[0188] Where: C is the equilibrium concentration (μg / m 3 ) ; q is the adsorption amount (μg / g); qm is the saturated adsorption amount (μg / g); b is the adsorption equilibrium constant; k is the Freundhch constant; 1 / n is the adsorption index (n is always greater than 1)
[0189] Figure 5 is a graph showing the relationship between the initial TVOC content and the adsorption amount of the highland barley straw adsorbent in Example 6, Figure 5 It was concluded that with the continuous increase of TVOC content, the adsorption amount of TVOC by highland barley straw adsorbent gradually increased within the experimental content range.
[0190] Figure 6 The isotherms of TVOC adsorption by highland barley straw adsorbent in Example 6 are shown in Figure 6. (a) is the Langmuir isotherm of TVOC adsorption by highland barley straw adsorbent, and (b) is the Freundlich isotherm of TVOC adsorption by highland barley straw adsorbent. Figure 6 (a)(b), combined with Table 6, it can be concluded that in the Freundlich model, the correlation coefficient R 2 It is closer to 1, that is, it is more inclined to the Freundlich isotherm adsorption model, indicating that the surface of highland barley straw adsorbent has many active sites and multi-molecular layer adsorption is dominant.
[0191] Table 6 Langmuir and Freundlich isotherm parameters of TVOC adsorption by highland barley straw adsorbent of Example 6
[0192]
[0193] b. Adsorption kinetics curve
[0194] Adsorption kinetics is used to determine the adsorption rate and adsorption mechanism. In the present invention, it is used to describe the adsorption rate of TVOC by highland barley straw adsorbent.
[0195] Generally, pseudo-first-order rate equation and pseudo-second-order rate equation are used for quasi-fitting:
[0196] Pseudo-first-order rate equation:
[0197] lg(q e -qt ) = lgq e -k1t / 2.303 (4)
[0198] Pseudo-second-order rate equation:
[0199] t / q t =1 / (k2q e 2 )+t / q e (5)
[0200] Where: q e is the equilibrium adsorption amount (μg / g);
[0201] q t is the TVOC adsorption amount at adsorption time t (μg / g); k1 is the pseudo-first-order adsorption rate constant (min -1 ); k2 is the pseudo-secondary adsorption rate constant (μg·g -1 ·min -1 ); t is the adsorption time (min); 1 / n is the adsorption index (n is always greater than 1);
[0202] With t(min) as the horizontal coordinate, q e (μg / g) is used as the ordinate to draw the adsorption kinetics curve.
[0203] Figure 7 The adsorption amount of TVOC by highland barley straw adsorbent of Example 6 changes with time. Figure 7 It was found that with the continuous increase of adsorption time, the removal rate of TVOC by highland barley straw adsorbent increased first and then decreased. When the adsorption time was about 120 minutes, the removal effect was the best.
[0204] Figure 8 The following are the fitting diagrams of the adsorption kinetic equations of TVOC by highland barley straw adsorbent in Example 6. (a) is the pseudo-first-order kinetic equation curve diagram, and (b) is the pseudo-second-order kinetic equation curve diagram. Figure 8 (a)(b), combined with Table 7, it can be concluded that the adsorption law of highland barley straw adsorbent for TVOC is highly consistent with the quasi-second-order kinetic model, and its adsorption process is mainly chemical adsorption and supplemented by physical adsorption.
[0205] Table 7 Example 6 The first and second order kinetic parameters of TVOC adsorption by highland barley straw adsorbent
[0206]
[0207] C. Adsorption thermodynamic curve
[0208] Fig. 9 is a curve diagram showing the variation of the adsorption amount of the highland barley straw adsorbent according to the adsorption temperature in Example 6, Fig. 9 It was observed that with the increase of adsorption temperature, the adsorption amount first increased and then decreased, indicating that there is an optimum temperature point to achieve the maximum adsorption amount.
[0209] The calculation formula for adsorption heat (ΔH) is:
[0210] InK C =△G0 / RT=△S0 / R-△H0 / RT (6)
[0211] K C =ρ1 / ρ2 (7)
[0212] Where: △G0 is the standard Gibbs free energy (KJ / mol); R is the thermodynamic gas constant, the value is J / (mol·K); T is the thermodynamic temperature (K); △H0 is the enthalpy variable of the reaction (KJ / mol); △S0 is the entropy variable [J / (mol·K)]; K C is the thermodynamic equilibrium constant; ρ1 is the mass concentration of TVOC gas molecules adsorbed on the adsorbent (μg / m 3 ).
[0213] Table 8 Thermodynamic parameters
[0214] T / K <![CDATA[ΔG0(KJ / mol)]]> <![CDATA[ΔH0(KJ / mol)]]> <![CDATA[ΔS0(J·mol -1 ·K -1 )]]> 293 -4.59 20.1930432 84.237 297 -4.76 20.1930432 84.237 299 -4.79 20.1930432 84.237 301 -5.26 20.1930432 84.237 303 -5.41 20.1930432 84.237
[0215] Depend on Fig.10 , Table 8 shows that the R2 of the fitting curve of the thermodynamic equation for the adsorption of TVOC by highland barley straw adsorbent is 0.7924, which is close to 1, indicating that the modified highland barley straw follows the laws of thermodynamics when adsorbing TVOC; and ΔH0>0 and ΔG0<0, indicating that the adsorption process of TVOC by highland barley straw adsorbent can be a spontaneous endothermic process.
[0216] (2) Horizontal comparative analysis
[0217] Test group: Example 6 Highland barley straw adsorbent, highland barley straw, diatomaceous earth, activated carbon, bamboo charcoal, macroporous resin AB-8 adsorb TVOC and measure the adsorption effect:
[0218] Fig.11 This is a comparison chart of the adsorption effect of different adsorbents on TVOC. Fig.11 The results showed that under the same conditions, highland barley straw adsorbent had the best adsorption effect on TVOC, which was significantly better than diatomaceous earth, activated carbon, bamboo charcoal, macroporous resin AB-8 and highland barley straw. According to the strength of the adsorption effect, the adsorption effect was in the order of highland barley straw adsorbent, diatomaceous earth, activated carbon, bamboo charcoal, macroporous resin AB-8 and highland barley straw. The two-factor interaction result (F=607.233, P<0.01) clearly showed that modified highland barley straw had the best adsorption effect.
[0219] Table 9 Two-factor ANOVA table
[0220]
[0221]
[0222] It can be seen from Table 9 that the effects of different adsorbents and different times on the adsorption effect are extremely significant. The combined effect of the two factors significantly affects the adsorption effect of the adsorbent on TVOC.
[0223] Table 10 Effect of different adsorbents on TVOC adsorption
[0224] Material Mean 5% significant level 1% extremely significant level Highland barley straw adsorbent 19.71 a A diatomite 8.3153 b B Activated carbon 6.4427 c C Bamboo charcoal 4.9227 d D Macroporous resin AB-8 4.536 e E Highland barley straw 3.1773 f F
[0225] It can be concluded from Table 10 that the adsorption effect of highland barley straw adsorbent on TVOC exceeds that of other materials, reaching a very significant level of 1%. Therefore, compared with other adsorbent materials, highland barley straw adsorbent has a significant advantage in the adsorption effect on TVOC. The F test and horizontal comparison show that highland barley straw adsorbent is significantly better than all other materials at a significance level of 1%.
[0226] (3) Desorption experimental test
[0227] The highland barley straw adsorbent after TVOC adsorption was spread out in the sun to dry. After high-temperature treatment for 2 hours, the adsorption experiment was repeated seven times in a row. The removal rate was measured each time to further explore its adsorption performance.
[0228] Fig.12 This is the analysis and regeneration diagram of highland barley straw adsorbent in Example 6. Fig.12 It was found that with the increasing number of desorption times, the adsorption effect of each subsequent adsorption decreased slightly; after the 7th desorption, the removal rate could still reach 10.44% (F=5125.73, P<0.01), indicating that the desorption and regeneration effect of highland barley straw adsorbent was very good, and the material could be desorbed and re-adsorbed multiple times with a high recycling rate.
[0229] Fig.13 The adsorption effect of highland barley straw adsorbent on TVOC prepared in Comparative Examples 1 to 5 is shown in FIG. Fig.13 It was concluded that the removal rate of TVOC by highland barley straw adsorbent fluctuated between 1% and 6%, and the yield of the adsorbent fluctuated significantly. When the NaOH concentration was 0.5 mol / L, the removal rate was as high as 6%; when it was 0.2-0.4 mol / L, the removal rate was as low as 1%. When the NaOH concentration was 0.4 mol / L, the yield of highland barley straw adsorbent was the lowest, and when the NaOH concentration was 0.1 mol / L, the yield of highland barley straw adsorbent was as high as 60%.
[0230] Fig.14The adsorption effect of highland barley straw adsorbent on TVOC prepared in Comparative Examples 6 to 10 is shown in FIG. Fig.14 It was found that when the mass concentration of ligninase was 4 mg / mL, the removal rate was the lowest value of 1%, and when the mass concentration was 8 mg / mL and 12 mg / mL, the removal rate reached a maximum value of 5%; when the mass concentration of ligninase was 4 mg / mL, the yield of highland barley straw adsorbent was the lowest, and when the mass concentration of ligninase was 16 mg / mL, the yield of highland barley straw adsorbent was the highest, reaching 80%.
[0231] Fig.15 The adsorption effect of highland barley straw adsorbent on TVOC prepared in Example 5 and Example 10 to Example 13 is shown in FIG. Fig.15 It was concluded that the yield of highland barley straw adsorbent was between 66% and 80%. The yield was lowest at 0.1 mg / mL of hemicellulase mass concentration, which was only 66%, and reached a peak of 80% at 0.2 mg / mL and 0.4 mg / mL. By observing the removal rate curve, when the TVOC content was 0.1 mg / mL, the removal rate was 2%, which was lower than 8% when the TVOC content was 0.3 mg / mL.
[0232] Fig.16 The adsorption effect of highland barley straw adsorbent on TVOC prepared in Comparative Examples 11 to 15 is shown in FIG. Fig.16 It was concluded that the overall yield of highland barley straw adsorbent tended to remain stable between 70% and 75%. The removal rate of highland barley straw adsorbent was as low as 2% when the cellulase mass concentration was 0.1 mg / mL, and reached a maximum of 6% at 0.15 mg / mL.
[0233] comprehensive Figure 13 to Figure 16 The yield of highland barley straw adsorbent and the removal effect of TVOC showed that the highland barley straw adsorbent prepared by potassium chloride assisted hemicellulase, i.e., the highland barley straw adsorbent prepared by Example 5 and Examples 10 to 13, was better than the highland barley straw adsorbent prepared by Comparative Examples 1 to 15.
[0234] Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0235] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a highland barley straw adsorbent, characterized in that: The following steps are involved: placing highland barley straw in a potassium chloride solution for salting out to soften and change the surface charge properties of the highland barley straw to obtain soaked highland barley straw; The soaked highland barley straw is placed in a hemicellulase solution for degradation to obtain degraded highland barley straw; wherein the mass concentration of the hemicellulase solution is 0.1 mg / mL to 0.5 mg / mL; The degraded highland barley straw is subjected to enzyme inactivation treatment, dried and crushed to obtain a highland barley straw adsorbent.
2. The method for preparing the highland barley straw adsorbent according to claim 1, characterized in that: The concentration of potassium chloride solution is 0.07 mol / L~0.24 mol / L.
3. The method for preparing the highland barley straw adsorbent according to claim 1, characterized in that: The method of salting out treatment is: soak the highland barley straw in potassium chloride solution for 25min to 35min.
4. The method for preparing the highland barley straw adsorbent according to claim 1, characterized in that: The highland barley straw was also steamed before the salting-out treatment.
5. A highland barley straw adsorbent prepared by the preparation method according to any one of claims 1 to 4.
6. The highland barley straw adsorbent according to claim 5, characterized in that: The particle size of the highland barley straw adsorbent is 18 meshes to 100 meshes.
7. Use of the highland barley straw adsorbent according to claim 5 or 6 in preparing a TVOC adsorbent.
8. The use of highland barley straw adsorbent in the preparation of TVOC adsorbent according to claim 7, characterized in that: The highland barley straw adsorbent is placed in an air atmosphere containing TVOC for adsorption treatment.
9. The use of highland barley straw adsorbent in the preparation of TVOC adsorbent according to claim 7, characterized in that: The ratio of the mass of the highland barley straw adsorbent to the amount of TVOC is 1g to 5g: 1.6mg / m 3 ~1.97 mg / m 3 .